Char Development and Settlement Project II, Bangladesh : April 1-June 30, 2000 ; Completion report, bridging period Oct 1, 1999-June 30, 2000 = Cara Unnaẏana o Basati Sthāpana Prakalpa 2. (Progress report (Char Development and Settlement Project II (Bangladesh)) ;, 2000)
With reference to Bangladesh.